Medicine Meets Virtual Reality 13 : the Magical Next Becomes the Medical Now - Westwood, James D. (Studies in health technology and informatics, 2005)
Robotics and intelligence networks allow the healer's sight, hearing, touch, and judgment to be extended across distance, as if by magic. The moments when scientific truth is suddenly revealed after lengthy observation, experimentation, and measurement is the real magic. This book documents these moments, which are human ingenuity in progress.